Gender norms and the marketing of seeds and ware potatoes in Malawi. - Mudege, Netsayi N.; Kapalasa, E.; Chevo, T.; Nyekanyeka, T.; Demo, P. (2015)
Gender dynamics shape and influence the nature of participation in, as well as the ability to benefit from, seed and ware potato markets in Malawi. 35 sex-disaggregated focus group discussions with farmers and 4 interviews with extension officers were conducted in Dedza and Ntcheu districts. Data on seed marketing and purchase, ware potato marketing, affordability, marketing decisions, and clients, as well as social norms and values that influence market participation by men and women were collected and analyzed using the Real Markets Approach focusing on social relations within markets. Results demonstrate that agricultural market interventions that do not address underlying social structures - such as those related to gender relations and access to key resources - will benefit one group of people over another; in this case men over women.